2019
DOI: 10.1002/mrm.27772
|View full text |Cite
|
Sign up to set email alerts
|

Conditional generative adversarial network for 3D rigid‐body motion correction in MRI

Abstract: westgrid.ca) and Compute Canada Calcul Canada (www.computecanada.ca).Purpose: Subject motion in MRI remains an unsolved problem; motion during image acquisition may cause blurring and artifacts that severely degrade image quality. In this work, we approach motion correction as an image-to-image translation problem, which refers to the approach of training a deep neural network to predict an image in 1 domain from an image in another domain. Specifically, the purpose of this work was to develop and train a cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
85
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(86 citation statements)
references
References 37 publications
1
85
0
Order By: Relevance
“…This was achieved by allowing the gradient calculated from the FCN classification loss to propagate back to the generator to implicitly convey the disease-related information to the generator. As a result, the classification loss that was propagated provided a momentum for the generator to generate images that contributed to 16 [6,20] 16 [6,20] 16 [4,20] 16 [7,20] 16 [6,20] 14 [7,20] [24,30] 23.5 [18,28] 30 [26,30] 26 [24,30] 23 [20,27] 29 [20,30] 22 [0,30] 29 [25,30] 18 [6,22] Three independent datasets including (a) the Alzheimer's Disease Neuroimaging Initiative (ADNI) dataset, (b) the Australian Imaging, Biomarker & Lifestyle Flagship Study of Ageing (AIBL), and (c) the National Alzheimer's Coordinating Center (NACC) were used for this study lower cross-entropy loss and thus facilitated better image classification. The generator of the GAN model consists of three 3D convolutional blocks in which each convolutional operation was followed by batch normalization and rectified linear unit (ReLu) activation.…”
Section: Deep Learning Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…This was achieved by allowing the gradient calculated from the FCN classification loss to propagate back to the generator to implicitly convey the disease-related information to the generator. As a result, the classification loss that was propagated provided a momentum for the generator to generate images that contributed to 16 [6,20] 16 [6,20] 16 [4,20] 16 [7,20] 16 [6,20] 14 [7,20] [24,30] 23.5 [18,28] 30 [26,30] 26 [24,30] 23 [20,27] 29 [20,30] 22 [0,30] 29 [25,30] 18 [6,22] Three independent datasets including (a) the Alzheimer's Disease Neuroimaging Initiative (ADNI) dataset, (b) the Australian Imaging, Biomarker & Lifestyle Flagship Study of Ageing (AIBL), and (c) the National Alzheimer's Coordinating Center (NACC) were used for this study lower cross-entropy loss and thus facilitated better image classification. The generator of the GAN model consists of three 3D convolutional blocks in which each convolutional operation was followed by batch normalization and rectified linear unit (ReLu) activation.…”
Section: Deep Learning Frameworkmentioning
confidence: 99%
“…Since its introduction, there has been a surge of interest in the application of GAN frameworks related to the brain. Some of the applications include image generation with improved properties such as achieving super resolution or better quality [6][7][8][9][10][11], data augmentation [12][13][14], segmentation [9,[13][14][15][16], image reconstruction [17][18][19][20], image-to-image translation [21][22][23][24], and motion correction [25,26]. While these important studies have demonstrated the exciting prospect of using GAN architectures, there is a limited amount of work that has focused on utilizing the generated images for subsequent tasks such as disease classification [27].…”
Section: Introductionmentioning
confidence: 99%
“…GANs have been used to synthesize strikingly realistic pictures of faces and inanimate objects (11,12). With respect to medical image data, GANs have shown promise across a wide range of applications (13), including simulated modality transformations (14)(15)(16)(17)(18), artifact reduction (19,20), and synthetic-image generation for supervised machine learning, thereby obviating patient-privacy protection of training data (21)(22)(23).…”
Section: Generative Adversarial Network (Gans)mentioning
confidence: 99%
“…Image generation can be conditional on a specific, which allows the cGAN model to encode particular patterns in the training process, so that the D network can generate output images with desired [11]. The cGAN architecture has been successfully applied to medical imaging tasks [12][13].…”
Section: A Deep Convolutional Generative Adversarial Networkmentioning
confidence: 99%